2018
DOI: 10.1038/s41394-018-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a ketogenic diet for improvement of neurological recovery in individuals with acute spinal cord injury: a pilot, randomized safety and feasibility trial

Abstract: Study design Longitudinal, randomized study. Objectives (1) Test the safety and feasibility of a ketogenic diet (KD) intervention in the acute stages of spinal cord injury (SCI), (2) assess the effects of a KD on neurological recovery, and (3) identify potential serum biomarkers associated with KD-induced changes in neurological recovery. Setting Acute care and rehabilitation facility. Methods The KD is a high-fat, low-carbohydrate diet that includes ≈70-80% total energy as fat. Seven participants with acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…In addition, a study by Streijger et al (2013) showed the critical role of ketones in neuroprotection by starting a KD four hours after cervical hemi-contusion in rats with SCI (19). Consistent with the published effects of a KD in rat models of SCI and in humans with hyperglycemia, our randomized pilot feasibility trial (20) showed that, compared with a standard hospital diet (SD), five weeks of KD improved upper extremity motor scores (Fig 1).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, a study by Streijger et al (2013) showed the critical role of ketones in neuroprotection by starting a KD four hours after cervical hemi-contusion in rats with SCI (19). Consistent with the published effects of a KD in rat models of SCI and in humans with hyperglycemia, our randomized pilot feasibility trial (20) showed that, compared with a standard hospital diet (SD), five weeks of KD improved upper extremity motor scores (Fig 1).…”
Section: Introductionsupporting
confidence: 75%
“…Because glutamate excitotoxicity, inflammation, and induction of apoptotic pathways lead to progressive degeneration in the spinal cord shortly after the injury, inhibition ofthese processes by ketone bodies may enhance neurological recovery after an SCI. In support of these hypotheses, we recently showed, for the first time, that compared with an SD, five weeks of KD improved upper extremity motor function in patients with acute SCI (figure 1)(20). In addition, a neuroinflammatory blood protein, fibrinogen, was present at lower levels in the KD serum samples than in the SD serum samples.…”
mentioning
confidence: 65%
“…While no studies that we are aware of have addressed the effects of KD on thoracic SCI or peripheral nerve injury, there have been reports of the beneficial effects of KD on the recovery of reaching behavior in high cervical injuries in both mouse studies (Streijger et al, 2013) and human studies (Yarar-Fisher et al, 2018). These effects on reaching behavior in mice were confined to supination and grasping, suggesting regional effects on the cervical motor circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have suggested that a KD might also be bene cial to humans with neurological disorders, such as Parkinson's disease, Alzheimer's disease, multiple sclerosis, and traumatic brain injury [11][12][13]. Multiple reports have revealed that a KD may exert neuroprotective effects after SCI [14][15][16][17][18][19]. For example, Tetzlaff et al found that KD improves forelimb motor function after SCI [14].…”
Section: Introductionmentioning
confidence: 99%